Self Healing Generasi Z: Bentuk Baru Perilaku Konsumtif Pada Mahasiswi FISIP ULM - Putri, Azmi Anugerah; Hidayah, Sri (Huma: Jurnal Sosiologi, 2024)
The Covid-19 pandemic is the beginning of the rise of the self healing trend among generation Z when all activities must be done from home, so many people need self healing. This study aims to determine the meaning of self healing and how self healing becomes consumptive behavior. The subjects of this research were female students of the Faculty of Social and Political Sciences, Lambung Mangkurat University. This research uses a qualitative approach with phenomenological research type. Data collection techniques using observation, interviews, and documentation. The research informants amounted to 18 people, who were obtained by snowball technique. The results showed that self healing became a habit during the Covid-19 pandemic which was finally difficult to abandon and is now a new form of consumptive behavior. Generation Z (female FISIP ULM students) interpret self healing as an obligation, a burden, a way to get recognition, and show themselves on social media. Self healing is used as a sign value that is consumed to show off a lifestyle. The consumption logic of Generation Z (female FISIP ULM students) is no longer on how self healing can provide complete healing, but is replaced by a need that must always be fulfilled. This research concludes that the meaning of self healing has shifted away from its true meaning. It is important for Generation Z students and social media users to wisely filter information and trends that can trigger consumptive behavior. Self healing should be about real self-healing, not just a trend on social media that encourages someone to do it until it becomes consumptive behavior.